2010
DOI: 10.1177/104063871002200218
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Polymerase Chain Reaction Assay for Detection and Quantification of Lawsonia Intracellularis

Abstract: Abstract. Lawsonia intracellularis, a causative agent of porcine proliferative enteropathy, is an obligate intracellular bacterium that is difficult to culture, propagate, and quantify. The intestinal epithelial cell line (IEC-18, derived from rat small intestine crypt cells) has been used to isolate and propagate this pathogen. However, the lack of rapid and simple quantification methods has led to mixed results when using the rat cell line, complicating Lawsonia studies. To overcome these limitations, a SYBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The above results suggest a decreased susceptivity to inhibition in RPA-FLD from feces in contrast to a greater susceptivity to inhibition in conventional PCR. Previous study has demonstrated that disease symptoms corresponded with higher fecal shedding of L. intracellularis detected by a SYBR green quantitative polymerase chain reaction (qPCR) assay after inoculating L. intracellularis -free pigs with 5 × 10 5 bacteria per pig [20]. Thus, the sensitivity in term of number of L. intracellularis in feces sample presented in this study provided a means to monitor L.intracellularis shedding from naturally or experimentally infected pigs.…”
Section: Discussionmentioning
confidence: 77%
“…The above results suggest a decreased susceptivity to inhibition in RPA-FLD from feces in contrast to a greater susceptivity to inhibition in conventional PCR. Previous study has demonstrated that disease symptoms corresponded with higher fecal shedding of L. intracellularis detected by a SYBR green quantitative polymerase chain reaction (qPCR) assay after inoculating L. intracellularis -free pigs with 5 × 10 5 bacteria per pig [20]. Thus, the sensitivity in term of number of L. intracellularis in feces sample presented in this study provided a means to monitor L.intracellularis shedding from naturally or experimentally infected pigs.…”
Section: Discussionmentioning
confidence: 77%
“…L. intracellularis can be cultured from homogenized intestinal tissue in cell lines including IEC-18 (rat small intestinal cells) and McCoy cells (mouse fibroblasts) (Lawson and Gebhart, 2000;Watarai et al, 2008). A quantitative PCR (qPCR) assay that is able to assess the growth of L. intracellularis in cultured cells has also been used to detect the organisms in pig fecal samples and could be used in other animal species (Drozd et al, 2010).…”
Section: Proliferative Enteropathymentioning
confidence: 99%
“…Subclinical infection is common [4], L. intracellularis can be demonstrated by PCR in animals vaccinated by an avirulent live vaccine [5] and the bacterial load in faeces could previously not be assessed in routine diagnostic work as the bacterium could only be cultivated and maintained in cell cultures [6]. Development of quantitative PCR (qPCR) tests for quantification of L. intracellularis in faeces [5,7-10] has now made it possible to determine the number of L. intracellularis bacteria in faeces on a routine basis. This may be useful for confirmation of L. intracellularis as the microbiological cause in porcine diarrhoea.…”
Section: Introductionmentioning
confidence: 99%